Access to environmental information: a driver of accountable governance in Morocco and Tunisia? - Annabelle Houdret; Irene Pasqua; Saâd Filali Meknassi (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
In Tunisia, Morocco and other North African countries, en¬vironmental problems increasingly lead to political protest. Industrial pollution and a lack of clean drinking water adversely impact the living conditions and income op¬portunities of already marginalised groups and trigger unrest. Environmental governance in the region is often highly centralised, and takes no consideration of the needs of the citizens in the use of natural resources. In a political context that remains unstable following the 2011 uprisings, the double challenge of mounting environmental problems and related social unrest calls for new approaches. Reinforcing accountable environmental governance could help, not only by addressing environmental problems and needs, but by contributing to the overall transformation of societal relationships towards more democratic (i.e. transparent, accountable and participative) governance in the longer term. Access to environmental information plays a crucial role in this regard: only if citizens know about availability, quality and use of natural resources, can they make informed choices and claim their rights. When public institutions address these rights, they can increase sustainable wealth for present and future generations. Institutions charged with strengthening accountability can also include citizens in their monitoring exercises, and help to hold public and private actors legally responsible for their decisions and behaviour. Related international standards can inform such reforms: the Universal Declaration of Human Rights, the Rio Declaration and the Aarhus Convention confirm the importance of access to environmental information. At national levels, environmental charters and Morocco's and Tunisia's new constitutions stress the need for participatory and accountable governance. As recent assessments in Morocco and Tunisia reveal, governments and development partners can support access to environmental information and thereby accountable governance. First, they can do this by strengthening accountable environmental governance and access to environmental information across sectors. This includes engaging democratic institutions in environmental issues and building up related capacities and know-how, supporting accountability organisations and rules, and improving citizens' and the administrations' understanding of new rights. It also entails empowering communities and forging new cross-sectoral coalitions, besides integrating the countries into international initiatives for accountable governance. Second, governments and development cooperation can support accountability in the environmental sector, including by taking advantage of international initiatives, such as the Sustainable Development Goals (SDGs). Climate mitigation and adaptation policies also provide opportunities for strengthening accountable environmental governance. Moreover, policy-makers need to be more aware of the links between environmental governance and its potential impact on human rights and political stability. Access to environmental information, related legal frameworks and institutional capacities also need further backing, including support to articulate related claims. Finally, comprehensive and transparent environmental and social impact assessments of public and private projects, and engaging protest movements in constructive dialogues with the administration and the private sector can help in preventing and addressing related social unrest.
Keywords: 330; Governance; Umwelt; Ökosysteme und Ressourcen